Leading tendencies in the development of cultural and spiritual identity of the peoples of Uzbekistan - Muminov, A.G.; Nazarov, K.; Xaynazarov, B.; Polvonov, H.; Ktaybekov, s (International Journal of Psychosocial Rehabilitation, 2020)
Interethnic harmony and tolerance are universal values. It defines national development in a country where people of different nationalities live, and thus serves as a guarantee of peace and stability. When we look at the history of the Uzbek people, we see that the ideals of tolerance, which is one of the qualities of the Uzbek people, have been magnificent. Our people have always been very generous and hospitable. The greatest wealth we have achieved over the years of independence is the peaceful and peaceful life of our people. In our country, such noble qualities as mutual respect, kindness and tolerance among people of all nations and nationalities, the principle of living in accordance with national and universal values is strengthening. Representatives of more than one hundred and thirty nationalities live in our country as children of a single family. As a result of the coexistence, co-existence and coexistence of so many nationalities and ethnic groups, each of them is enriched in the spirit and culture of the nation, and the interconnectedness of our multinational people is growing. The conditions for their observance of constitutional rights and freedoms, legal interests, education, occupation and occupation of their own interests and abilities are created. The issue of inter-ethnic tolerance and spiritual values has a strong legal basis and Article 18 of the Constitution of the Republic of Uzbekistan states that “All citizens of the Republic of Uzbekistan shall enjoy the same rights and freedoms, sex, race, regardless of nationality, language, religion, social origin, belief, personal or social status. This article reviews the revival of spiritual and cultural values in Uzbekistan over the years of independence and the state policy pursued in this regard.